Hepatic glycosphingolipid deficiency and liver function in mice - Jennemann, Richard; Rothermel, Ulrike; Wang, Shijun; Sandhoff, Roger; Kaden, Sylvia; Out, Ruud; van Berkel, Theo J.; Aerts, Johannes M.; Ghauharali, Karen; Sticht, Carsten; Gröne, Hermann-Josef (Hepatology, 2010)
Recent studies have reported that glycosphingolipids (GSLs) might be involved in obesity-induced insulin resistance. Those reports suggested that inhibition of GSL biosynthesis in animals ameliorated insulin resistance accompanied by improved glycemic control and decreased liver steatosis in obese mice. In addition, pharmacologic GSL depletion altered hepatic secretory function. In those studies, ubiquitously acting inhibitors for GSL biosynthesis have been used to inhibit the enzyme Ugcg (UDP-glucose:ceramide glucosyltransferase), catalyzing the first step of the glucosylceramide-based GSL-synthesis pathway. In the present study a genetic approach for selective GSL deletion in hepatocytes was chosen to achieve complete inhibition of GSL synthesis and to avoid possible adverse effects caused by Ugcg inhibitors. Using the Cre/loxP system under control of the albumin promoter, GSL biosynthesis in hepatocytes and their release into the plasma could be effectively blocked. Deletion of GSL in hepatocytes did not change the quantity of bile excretion through the biliary duct. Total bile salt content in bile, feces, and plasma from mutant mice showed no difference as compared to control animals. Cholesterol concentration in liver, bile, feces, and plasma samples remained unaffected. Lipoprotein concentrations in plasma samples in mutant animals reached similar levels as in their control littermates. No alteration in glucose tolerance after intraperitoneal application of glucose and insulin appeared in mutant animals. A preventive effect of GSL deficiency on development of liver steatosis after a high-fat diet was not observed. Conclusion: The data suggest that GSL in hepatocytes are not essential for sterol, glucose, or lipoprotein metabolism and do not prevent high-fat diet-induced liver steatosis, indicating that Ugcg inhibitors exert their effect on hepatocytes either independently of GSL or mediated by other (liver) cell types. HEPATOLOGY 2010
First published: 22 April 2010
Gesehen am 02.08.2023